Mandate for Armenia - United States. President (1913-1921 : Wilson) (My University)
In 1920, a "Mandatory for Armenia" (or American Mandate) was proposed under the League of Nations to provide protection, economic aid, and administrative oversight to the newly independent First Republic of Armenia. Although President Woodrow Wilson strongly supported it, the U.S. Senate rejected the mandate in June 1920, leading to the failure of the Treaty of Sèvres and the subsequent sovietization of Armenia Item
Message from the President of the United States, requesting that the Congress grant the executive power to accept for the United States a mandate for Armenia
[Washington, Govt. print. off., 1920] - 3 p. : 24 cm.
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ԱՄՆ-ի Կոնգրեսի գրադարանից
https://www.loc.gov/item/20026615/
Keywords: United States-Foreign relations-Armenia; Armenia (Republic)-Foreign relations-United States